2018
DOI: 10.3389/fmars.2018.00316
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenose Dolphins and Antillean Manatees Respond to Small Multi-Rotor Unmanned Aerial Systems

Abstract: Unmanned aerial systems (UASs) are powerful tools for research and monitoring of wildlife. However, the effects of these systems on most marine mammals are largely unknown, preventing the establishment of guidelines that will minimize animal disturbance. In this study, we evaluated the behavioral responses of coastal bottlenose dolphins (Tursiops truncatus) and Antillean manatees (Trichechus manatus manatus) to small multi-rotor UAS flight. From 2015 to 2017, we piloted 211 flights using DJI quadcopters (Phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 60 publications
4
91
1
Order By: Relevance
“…Nonetheless, research efforts should be mindful of minimizing the disturbance on dolphins in any attempts to obtain samples (Hodgson and Koh , Ramos et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, research efforts should be mindful of minimizing the disturbance on dolphins in any attempts to obtain samples (Hodgson and Koh , Ramos et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), with no or limited disturbance (but see Ramos et al. ). However, the count data collected through UAS surveys only provide information about how many, when, and where surface‐associated wild animals are spotted; these data offer limited to no information about how the organisms react to biotic (e.g., predators, human disturbances, or fisheries activities) or abiotic factors at different temporal and spatial scales.…”
Section: Equipment and Applicationmentioning
confidence: 99%
“…Recent technological advancements have allowed researchers to expand the range of questions being addressed using UASs-in particular, the development of novel image processing techniques that not only improve the quality of the data but can also be done in a timely manner, allowing for aerial surveys at ever finer scales. Traditionally, aerial surveys using UASs equipped with high-resolution video cameras have been used in studies of marine wildlife to assess their distribution, density, and abundance Kiszka et al 2016;Rieucau et al 2018), with no or limited disturbance (but see Ramos et al 2018). However, the count data collected through UAS surveys only provide information about how many, when, and where surface-associated wild animals are spotted; these data offer limited to no information about how the organisms react to biotic (e.g., predators, human disturbances, or fisheries activities) or abiotic factors at different temporal and spatial scales.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Manned aerial surveys can cover larger areas and fly longer compared to small drones, but lack the maneuverability of multirotor drones and the potential of drones for extensive sampling in small areas and at low altitudes (Colefax et al 2018). Drones have been successfully used in a broad range of applications including the detection and counting of marine megafauna (Hodgson et al 2017); photogrammetry to assess cetacean body condition (Durban et al 2015, Christiansen et al 2016; collection of exhaled breath condensate from large baleen whales (Domínguez-Sánchez et al 2018), and behavioral studies (Ramos et al 2018, Torres et al 2018. Drone-based photo-ID studies of bow head whales Balaena mysticetus (Koski et al 2015), killer whales Orcinus orca (Durban et al 2015), and seals (Pomeroy et al 2015) have confirmed the efficacy of this method for identifying numerous marine mammals, but its ap plication to sirenians has not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%